Pengaruh Pemberian Natrium Bikarbonat terhadap Kelelahan dan Nyeri Otot setelah Melakukan Treadmill - Fath Arina Fahma; Cholis Abrori; Hairrudin Hairrudin (Pustaka Kesehatan, 2019)
Treadmill is a physical exercise that caused a metabolic transition from aerobic into anaerobic. The aim of this study was to determine the effect of sodium bicarbonate to reduce fatigue and muscle pain after treadmill. This study used a time-series design with 20 selected samples from undergraduate student population of the Faculty of Medicine, Jember University. Samples consumed 100mg/kgBW NaCl (placebo) and NaHCO3 300mg/kgBW then perform a treadmil protocol until it reached maximum muscle fatigue. The results showed that the average treadmill of the treatment group (778,1±121,21 seconds) was longer than control group (717,7±93,02 seconds). The intensity of acute pain as measured by VAS (Visual Analog Scale) treatment group was lower (44,7±22,47 units) than control (55,4±19,97 units). So this study inferred that NaHCO3 can reduce fatigue and acute pain intensity after treadmill.